2016
DOI: 10.1136/bmjopen-2015-009895
|View full text |Cite
|
Sign up to set email alerts
|

Caught between intending and doing: older people ideating on a self-chosen death

Abstract: ObjectivesThe aim of this paper is to provide insight into what it means to live with the intention to end life at a self-chosen moment from an insider perspective.SettingParticipants who lived independent or semidependent throughout the Netherlands.Participants25 Dutch older citizens (mean age of 82 years) participated. They were ideating on a self-chosen death because they considered their lives to be no longer worth living. Inclusion criteria were that they: (1) considered their lives to be ‘completed’; (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 24 publications
1
43
1
1
Order By: Relevance
“…Driven by the outcomes of our research (and not by prefixed ideological ideas), we tend to favour restraint and qualify the public debate: the results have given insight into the shortcomings in the prevailing conception of people as independent, autonomous and self-determining agents; the need for due consideration of all ambiguities present in the wish to die; and the inadequacy of considering this wish to die to be an individual problem (van Wijngaarden et al, 2016a). Besides, we have suggested that addressing the social and positional aspects of the wish to die might be a more appropriate response to the concerns of these people than offering them a legal opportunity to die (van Wijngaarden et al, 2015a).…”
Section: The Uneasy Moral Experience Of Threatening a Person's Self-nmentioning
confidence: 98%
See 1 more Smart Citation
“…Driven by the outcomes of our research (and not by prefixed ideological ideas), we tend to favour restraint and qualify the public debate: the results have given insight into the shortcomings in the prevailing conception of people as independent, autonomous and self-determining agents; the need for due consideration of all ambiguities present in the wish to die; and the inadequacy of considering this wish to die to be an individual problem (van Wijngaarden et al, 2016a). Besides, we have suggested that addressing the social and positional aspects of the wish to die might be a more appropriate response to the concerns of these people than offering them a legal opportunity to die (van Wijngaarden et al, 2015a).…”
Section: The Uneasy Moral Experience Of Threatening a Person's Self-nmentioning
confidence: 98%
“…Besides, it turned out that the wish to die was not at all clear, coherent and unambiguous; rather it was characterized by ambivalent feelings of being torn, expressed in words like: 'dilemma' , 'doubt' , 'a difficult balancing act' and 'a split position ' (van Wijngaarden, Leget, & Goossensen, 2016a). Thus, after a putatively rational decision had been made (that life was considered to be over), all kinds of ambivalences and ambiguities remained present (van Wijngaarden et al, 2016a).…”
Section: The Uneasy Moral Experience Of Threatening a Person's Self-nmentioning
confidence: 99%
“…4 At the same time, two of us conducted an independent in-depth study into the experiences of older people who consider their lives completed and do not wish to continue living. [23][24][25][26] This study has shown that completed life should be understood as "a tangle of inability and unwillingness to connect to life (to themselves, others, and the world) resulting in the experience that life is no longer worth living and death is preferred over life." 23 Those studied had no evidence of a severe physical or mental disease, but their disconnectedness arose from a profound sense of loneliness, the pain of not mattering, the growing inability to express themselves, existential and physical fatigue, and aversion to feared dependence and loss of control.…”
Section: Limited Evidencementioning
confidence: 99%
“…It is highly complicated-if not impossible-to establish whether the wish to die is truly consistent over time and without any (internalised) external pressure, whether the non-medical suffering is insoluble, and whether enabling an assisted death correctly addresses the (partly existential and social) needs and concerns in the lives of these older people. [23][24][25][26] In addition, allowing healthy older people the right to die might increase social pressure on this age group and reinforce negative ideas about old age. 24 Such concerns have led the medical profession, including the Dutch Association of Psychologists, 31 Dutch Nurses' Association, 32 and Royal Dutch Medical Association, 33 to raise objections to the governmental proposal.…”
Section: Implications Of Proposed Lawmentioning
confidence: 99%
“…However, 5%–30% of older people who wish to die have no psychiatric or depressive disorder (Rurup, Deeg et al., ; van Wijngaarden, Leget, & Goossensen, ). Most older people who wish to die probably consider suicide unacceptable, as it is associated with despair and mutilation (van Wijngaarden, Leget, & Goossensen ). However, differences between older patients who wish to die and those who are suicidal have been described (Kim, Bogner, Brown, & Gallo, ).…”
Section: Introductionmentioning
confidence: 99%